OPTIMASI BIAYA TRANSPORTASI PADA UKM DI KOTA BATAM - Sugianto, Welly; Susanti, Elva (Teknik Industri Unikom, 2021)
This research was conducted at UKM Jovelyn in Batam city. Jovelyn's UKM produces various kinds of cakes and is marketed in markets in Batam City. The UKM opened 4 branches and marketed its products to 7 markets in the city of Batam. Product distribution is still random and not properly regulated. This resulted in a very large transportation cost, up to 1/3 of the total production cost. This shows that product transportation is still not carried out effectively and efficiently. The transportation problem is converted into a mathematical form so that the problem can be solved by the transportation method. The transportation method aims to minimize the objective function which is a function of transportation costs. The transportation method is basically the same as the linear program where at each iteration a selection is made to enter the basic variabel and leave the basic variabel. There are several iteration methods, namely the northwest corner method, minimum cost method, genetic algorithm, Vogel's approximation method, minimum row method, Russell's approximation method and column minimum method. Previous research has shown that the Vogel's approximation method, and Russell's approximation method are more efficient and accurate. This study uses both methods and a sensitivity analysis is performed to optimize the calculation results. The sensitivity analysis aims to determine the extent to which the objective function constants and the constraint function constants can change Keywords: Transportation, Sensitivity, SME